Uso de trampas con feromonas sintéticas sexuales para el control del gusano cogollero (Spodoptera frugiperda), en el cultivo de maíz (Zea mays). - Cano Barco, Joel Fabian (2019)
SUMMARY "Use of traps with synthetic sex pheromones for the control of the armyworm Spodoptera frugiperda." AUTHOR: Joel Fabian Cano Barco TUTOR: Ing. Agr. Marlon López Izurieta, MsC. The present work consists in the compilation of information concerning a technique that is within the ethological control of pests; the management and control of spodptera frugiperda by using its sexual pheromone with the main component or attractant (Z) -9-tetradecenyl-1-ol-acetate, (Z-9-TDA) being identified. Which with other components such as Z-7dodecenyl-1-ol-acetate (Z-7DDA); and Z-9 dodecenyl-acetate (Z-9-DDA), it is possible to synthesize and take advantage of the process of pheromonal attraction of the male insects of Spodoptera frugiperda by using so-called traps, these traps are used to monitor and control the populations of the males of Spodoptera frugiperda. The present investigative work was developed in the "Faculty of Agricultural Sciences" of the Technical University of Babahoyo Province of Los Ríos. And based on what was consulted and developed in the present investigation, it is concluded that the use of pheromone traps is a technique to control populations but not to completely eradicate the pest; so it is necessary to apply all the processes, tactics and techniques of integrated pest management to avoid infestations of the insect to be controlled and, above all, to avoid the risk of resistance to traditionally used insecticides Keywords: pheromone, tetradecenyl; acetate; traps; Spodoptera frugiperda.